Detection of changes in the DNA-methylation patterns of cryopreserved apices of chrysanthemum - Martín, Carmen; Benito, M. Elena González (MTT, 2008)
Cryopreservation techniques allow long-term preservation of vegetatively propagated plants using in vitro-grown explants (e.g. shoots apices), from which the whole plants can be obtained. However, there is concern about the possible occurrence of somaclonal variation induced either by the in vitro procedures, used before or after cryostorage, or by the cryoprotection procedures. Some studies have already revealed that in vitro conservation techniques are associated with changes in the DNA methylation state (e.g. 2), and those changes have been related to somaclonal variation. There are evidences that epigenetic changes, as differences in the methylation pattern of DNA, play a role in the occurrence of somaclonal variation through, for example, activation of transposable elements and silencing of genes, however the exact mechanism of this process remain unknown (3). Genetic stability of cryopreserved chrysanthemum apices using RAPDs markers was evaluated in a previous work (4), founding in this study a somaclon between the regenerated material. From those results, techniques to detect possible changes in the DNA-methylation patterns of the cryopreserved apices have been developed in our laboratory. The detection of changes in the DNA-methylation pattern in somaclonal variation studies using the technique CRED-RA (coupled restriction enzyme digestion and random amplification; 1) is evaluated in this work. The technique is based in the capability of the restriction enzymes MspI y HpaII to cleave the same sequence (5 CCGG 3 ), but showing differential sensitivity to the presence of methyl residues. HpaII does not cut the sequence when any of the two residues of C are methylated, while MspI cuts the sequence when the internal C is methylated (5 CmCGG 3 ). Subsequent PCR amplification of the digested DNA may reveal differences in the methylation pattern. Ten samples from the cryopreserved chrysanthemum apices were studied (6 of them from the encapsulation-dehydration technique, and the other 4 from the vitrification technique), together with their corresponding pre-cryopreservation controls. The technique reveals its capability to show differences in the DNA-methylation pattern when used in the study of genetic stability of cryopreserved material. Differences between cryopreserved samples and their controls were found, mainly in samples deriving from the encapsulationdehydration technique.
Keywords: Ka; in vitro-grown explants; somaclonal variation; genetic stability; encapsulationdehydration; vitrification